2016
DOI: 10.1186/s13660-016-1141-x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simultaneous algorithms for the split equality problem with applications

Abstract: The split equality problem has board applications in many areas of applied mathematics. Many researchers studied this problem and proposed various algorithms to solve it. From the literature we know that most algorithms for the split equality problems came from the idea of the projected Landweber algorithm proposed by Byrne and Moudafi (Working paper UAG, 2013), and few algorithms came from the idea of the alternating CQ-algorithm given by Moudafi (Nonlinear Anal. 79:117-121, 2013). Hence, it is important and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Employing arguments which are similar to those used in Remark 3.4 , comparing ( 69 ) and (2.48) in [ 15 ], we conclude that Algorithm 3.2 (I) has a better contraction property than the hybrid alternating CQ-algorithm in [ 15 ].…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…Employing arguments which are similar to those used in Remark 3.4 , comparing ( 69 ) and (2.48) in [ 15 ], we conclude that Algorithm 3.2 (I) has a better contraction property than the hybrid alternating CQ-algorithm in [ 15 ].…”
Section: Resultsmentioning
confidence: 72%
“…Inspired by Algorithm 2.2 in [ 15 ] and based on Algorithm 3.1 , we present two semi-alternating projection algorithms, whose name comes from an alternating technique taken in the first step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Yao et al [28,29] extended the regularization method to approach the solution of SFP (4). Some works [30][31][32][33][34][35][36] also developed generalized fixed point algorithms which can be applied to approach the solution of SFP. In particular, the iterative scheme, expressed as the following Equation (8), proposed by Hong and Huang [32], has shown that it can efficiently approach the solution of SFP: Theorem 3.…”
Section: Algorithms For the Solution Of Peic And The Related Eco-friementioning
confidence: 99%